2022
DOI: 10.1155/2022/4710868
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Bidding Scheduling of a Price-Maker Cascade Hydropower Station Based on Supply Function Equilibrium

Abstract: How cascade hydropower stations (CHSs) play the electricity market game is regarded as an important issue. The majority of the work to date has focused on short-term horizons and several simplifications in the hydropower system. If future prices are expected to be higher than the current price, CHSs with large reservoirs allow the bidder to postpone energy production for a longer time scale, such as several months or more, which generally matches with the regulation period of the reservoir. Rejecting the assum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…Initial and end reservoir volumes constraints: Initial reservoir volume is the available water in the reservoir at the beginning of one operating day, and end reservoir volume is the remaining water after one operating day. The study considers the same value for the two factors as shown in the following equation [ 49 ]: Where. = Initial volume of the reservoir in the m th PSHEP = Volume of the reservoir in the m th PSHEP at the end of the last interval …”
Section: Problem Formulationmentioning
confidence: 99%
“…Initial and end reservoir volumes constraints: Initial reservoir volume is the available water in the reservoir at the beginning of one operating day, and end reservoir volume is the remaining water after one operating day. The study considers the same value for the two factors as shown in the following equation [ 49 ]: Where. = Initial volume of the reservoir in the m th PSHEP = Volume of the reservoir in the m th PSHEP at the end of the last interval …”
Section: Problem Formulationmentioning
confidence: 99%